Breaking the Size Limitation of Directly‐Synthesized PbS Quantum Dot Inks Toward Efficient Short‐wavelength Infrared Optoelectronic Applications. Issue 17 (17th March 2023) - Liu, Yang; Gao, Yiyuan; Yang, Qian; Xu, Gao; Zhou, Xingyu; Shi, Guozheng; Lyu, Xingyi; Wu, Hao; Liu, Jun; Fang, Shiwen; Ullah, Muhammad Irfan; Song, Leliang; et al.
Abstract: PbS quantum dots (QDs) are promising building blocks for solution‐processed short‐wavelength infrared (SWIR) devices. The recently developed direct synthesis of semi‐conductive PbS QD inks has substantially simplified the preparation processing and reduced the material cost, while facing the challenge to synthesize large‐size QDs with absorption covering the SWIR region. Herein, we for the first time realize a low‐cost, scalable synthesis of SWIR PbS QD inks after an extensive investigation of the reaction kinetics. Finally, based on these PbS SWIR QD inks, the solar cell demonstrates a record‐high power conversion efficiency (PCE) of 1.44 % through an 1100 nm cutoff silicon filter and the photodetector device shows a low dark current density of 2×10 −6 A cm −2 at −0.8 V reverse bias with a high external quantum efficiency (EQE) of 70 % at ≈1300 nm. Our results realize the direct synthesis of low‐cost and scalable SWIR QD inks and may accelerate the industrialization of consumer SWIR technologies. Abstract : A low‐cost, scalable synthesis of short‐wavelength infrared (SWIR) PbS quantum dot (QD) inks is realized after an extensive investigation of the reaction kinetics. Based on these PbS SWIR QD inks, SWIR solar cells and photodetector devices are fabricated, demonstrating record‐high efficiency. The direct synthesis of low‐cost and scalable SWIR QD inks may accelerate the industrialization of consumer SWIR technologies.